Hershberger Assays for Di-2-ethylhexyl Phthalate and Its Substitute Candidates - Kim, Hee-Su (Dev Reprod, 2018)
In the present study, we employed Hershberger assay to determine possible androgenic or antiandrogenic activities of three di-2-ethylhexyl phthalate (DEHP) substitute candidates. The assay was carried out using immature castrated Sprague–Dawley male rats. After 7 days of the surgery, testosterone propionate (TP, 0.4 mg/kg/day) and test materials (low dose, 40 mg/kg/day; high dose, 400 mg/kg/day) were administered for 10 consecutive days by subcutaneous (s.c.) injection and oral gavage, respectively. Test materials were DEHP, 2-ethylhexyl oleate (IOO), 2-ethylhexyl stearate (IOS) and triethyl 2-acetylcitrate (ATEC). The rats were necropsied, and then the weights of five androgen-dependent tissues [ventral prostate, seminal vesicle, coagulating glands, levator ani-bulbocavernosus (LABC) muscle, paired Cowper’s glands, and glans penis] and four androgen-insensitive tissues (kidney, adrenal glands, spleen and liver) were measured. All test materials including DEHP did not exhibit any androgenic activity in the assay. On the contrary, antiandrogen-like activities were found in all test groups, and the order of the intensity was ATEC < DEHP < ISO < IOO in the five androgen-sensitive tissues. There was no statistical difference between low dose treatment and high dose treatment of all replacement candidate groups. In DEHP groups, high dose treatment exhibited significant weight gains in LABC and Glan Penis. There was no statistical difference in androgen-insensitive tissue measurements. Since the effects of ATEC treatment on the accessory sex organs were much less or not present at all when compared to those of DEHP, ATEC could be a strong candidate to replace DEHP. IOO treatment brought most severe weight reduction in all of androgen-sensitive tissues, so this material should be excluded for further screening of DEHP substitute selection.